Perbandingan Metode Recurrent Neural Network (RNN) dan Long Short-Term Memory (LSTM) untuk Prediksi Curah Hujan - Hermawan, Taufan; Zuliarso, Eri (Forum Kerjasama Pendidikan Tinggi, 2025)
The increase in extreme rainfall intensity due to climate change has caused Batang Regency to become a hydrometeorological disaster-prone area. This research aims to build an day rainfall prediction model using Recurrent Neural Network (RNN) and Long Short-Term Memory (LSTM) based on BMKG historical data. The model is evaluated using Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) metrics. The results show that LSTM has higher accuracy than RNN, with an RMSE: 0.1036 | MAE: 0.0730. Meanwhile, RNN obtained an RMSE: 0.1035 | MAE: 0.0763. LSTM is also more stable in predicting temperature, direction, and wind speed variables. These findings show that LSTM is more effective for weather time series data and can be used as a basis for developing data-based disaster early warning systems in local areas.